Screening and in silico profiling of α - amylase (3m07) D anti-diabetic activity in the elucidated compounds of tecomaria capensis - MADHURILATHA THADANKI; PAVAN KUMAR CHADALAWADA; POOJA.B (International Journal of Pharma and Bio Sciences, 2018)
Diabetes mellitus is a common problem in most of the countries, especially in India where 90-95 % people have diabetes. It occurs due to inadequate insulin levels. Insulin is essential for maintaining blood glucose level which is essential for the body. When inadequate amount of insulin is produced, it has to be compensated by administration of insulin injections which is a painful procedure. So now a days, as there is a renewed interest in the traditionally used herbal drugs, the present study aims to screen the identified constituents of Tecomaria capensis for determining the potent constituent for antidiabetic activity using in-silico approach. The elucidated compounds were evaluated for the antidiabetic activity using in-silico Docking method. The receptor was analyzed for the active site and pocket finder tools. The amino acids such as Arg-307, Ile-291, Thr-225 and Asp-264 were predicted as active site binding residues. Docking studies were done through MVD (Molegro Virtual Docker) software. Out of six compounds, two compounds from leaves of Tecomaria capensis showed good docking profiles with Alpha - Amylase (3M07) D. Finally, the result from the study demonstrates that the 3, 7-dimethyloct-6-en-1-ol possess potent anti-diabetic activity against Type-II diabetes mellitus through drug action on Alpha - Amylase inhibition system.